Metamorphosing with Selkies: Shape-Shifting Instabilities in the Self-Conscious Anthropocene - McFarland, Sarah E. (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
This article deploys the inspirational figure of the selkie toward emphasizing non-hierarchical and sustainable co-existences between various species, ecosystems, and human beings, a necessary perspective in light of climate change, biodiversity loss, and species extinctions. The selkie wife story exposes the consequences of exceptionalist hierarchies, including those that structure nature as subordinate, animals as subordinate, and women as subordinate. Challenging this discriminatory thinking, the seal folk model accomplishes at least four things that are vital to its function as a traditional Irish folktale and to the ethical considerations it produces in the self-conscious Anthropocene. At its foundation lies a flexible worldview that accepts species ambiguity, contrasting with representations of biological others that fix their bodies as landscapes of control and abuse; the story itself is a warning against arrogance and domination, and is a rebuke of imperialism; and finally, it develops a clear lesson about how to be a proper person.Here I radically renegotiate human exceptionalism and the ontologies that illusion supports by turning to selkie myths and other stories of shapeshifting women to imagine alternative ways of thinking and living in the self-conscious Anthropocene in productive and collaborative ways.